Underwater Resurrection Routing Synergy using Astucious Energy Pods - Ashraf, Shahzad; Raza, Asif; Aslam, Zeeshan; Naeem, Hamad; Ahmed, Tauqeer (Universitas Muhammadiyah Yogyakarta, 2020)
The accomplishment of sustainable communication among source and destination sink node is a rigors challenge and even establishing bodacious communication link between these nodes is nothing short of a miracle because data routes are governed by the underwater environment. Energy consumption has a significant influence as all active devices rely on the battery. As cost-effective data packet transmission is established as a norm, no charging or replacement can be achieved. Hop link evaluation and shrewd connection discovery by way of a resurrecting linking element were just a genuinely grim task, and only feasible to create the extra powered energy pods (URR-SAEP) that had never been carried out before after detailed study. After packet transfer, the sensor node performs the link inspection process, and when a link is deemed shaky at less than or equivalent to 50 percent of capacity, the target node incorporates its residual capacity status and returns it to the source node that attaches other unoptimizable energy pods to improve only the targeted node link from 50 percent to 90 percent. Performance evaluation using NS2 with Aqua-Sim 2.0 simulator has been obtained comparing with DBR and EEDBR protocols in terms of point-to-point delay, Packet dissemination ratio, Network lifespan and Energy Diminution.